Body Painting: Memadukan Seni, Kecantikan, dan Performansi dalam Bentuk Seni Visual - Hartawati, Ni Putu Wulan (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
Body painting has emerged as an intriguing phenomenon in contemporary art and tourism, combining elements of visual art, attractiveness, and performance. This research investigates integrating these elements into a single piece of art and its influence on the tourism industry, model empowerment, and body commodification, with a particular emphasis on Bali. The qualitative research methodology involves in-depth interviews and observations of artists, models, and audiences in the context of body painting performances. The study results demonstrate that body painting is a visual art form and a performance activity that directly engages the audience. The fact that models may use their bodies as a means of artistic expression gives them a sense of empowerment.Furthermore, even though body painting retains its artistic significance, it is considered a commodity in Bali's tourism sector. This research enhances the comprehensive understanding of body painting, presents novel concepts regarding the interplay between art, performance, and economy, and paves the way for additional investigation into body art within a worldwide social and cultural framework. In conclusion, body painting is a multifaceted art form that enhances both the realm of visual arts and the domain of body art.